Nogo-A aggravates oxidative damage in oligodendrocytes - Yang-Yang Wang; Na Han; Dao-Jun Hong; Jun Zhang (Neural Regeneration Research, 2021)
Nogo-A is considered one of the most important inhibitors of myelin-associated axonal regeneration in the central nervous system. It is mainly expressed by oligodendrocytes. Although previous studies have found regulatory roles for Nogo-A in neurite outgrowth inhibition, neuronal homeostasis, precursor migration, plasticity, and neurodegeneration, its functions in the process of oxidative injury are largely uncharacterized. In this study, oligodendrocytes were extracted from the cerebral cortex of newborn Sprague-Dawley rats. We used hydrogen peroxide (H2O2) to induce an in vitro oligodendrocyte oxidative damage model and found that endogenously expressed Nogo-A is significantly upregulated in oligodendrocytes. After recombinant virus Ad-ZsGreen-rat Nogo-A infection of oligodendrocytes, Nogo-A expression was increased, and the infected oligodendrocytes were more susceptible to acute oxidative insults and exhibited a markedly elevated rate of cell death. Furthermore, knockdown of Nogo-A expression in oligodendrocytes by Ad-ZsGreen-shRNA-Nogo-A almost completely protected against oxidative stress induced by exogenous H2O2. Intervention with a Nogo-66 antibody, a LINGO1 blocker, or Y27632, an inhibitor in the Nogo-66-NgR/p75/LINGO-1-RhoA-ROCK pathway, did not affect the death of oligodendrocytes. Ad-ZsGreen-shRNA-Nogo-A also increased the levels of phosphorylated extracellular signal-regulated kinase 1/2 and inhibited BCL2 expression in oligodendrocytes. In conclusion, Nogo-A aggravated reactive oxygen species damage in oligodendrocytes, and phosphorylated extracellular signal-regulated kinase 1/2 and BCL2 might be involved in this process. This study was approved by the Ethics Committee of Peking University People’s Hospital, China (approval No. 2018PHC081) on December 18, 2018.